Polyamide/silica hybrid materials by anionic melt polymerization of lactam-substituted silane monomers with ε-caprolactam. (April 2019) - Nagel, Kevin; Spange, Stefan
Graphical abstract: Highlights: Formation of PA 6 and silica by anionic polymerization of lactam-substituted silanes Activating effect of silanes on anionic lactam polymerization. Decomposition of silanes to N-iminolactams enables the coupled formation of PA 6 and silica. Improvement of thermal stability compared to unfilled polyamide 6. Abstract: Polyamide 6/silica hybrid materials are fabricated by the activated anionic polymerization of ε -caprolactam ( ε -CL) with lactam-substituted silane monomers Si( ε -CL)4, Me2 Si( ε -CL)2 and Me3 Si( ε -CL), respectively. All three silane monomers are excellent activators for the anionic ε -caprolactam polymerization initiated by EtMgBr, resulting in short reaction times of a view minutes and high polymer yields. Studies on the thermal decomposition behavior of the lactam containing silanes indicate the formation of N -iminolactams, which influence the activation process as well as the pathway of the inorganic filler formation. The molecular structure and morphology of the hybrid materials have been investigated by solution and solid-state NMR and FTIR spectroscopies as well as electron microscopy and size exclusion chromatography measurements. As consequence, lactam-substituted silane monomers serve both as activator and reactant in the synthesis of PA/silica and related hybrid materials.